The Formation of Students' Readiness for Research Work in Conditions of Mathematics and Informatics Integration - I E Bystryenina (Peoples' Friendship University of Russia (RUDN University), 2011)
In the article the model of the students' preparedness formation for research activity on the basis of the integration of Mathematics and Informatics is presented, the principles and pedagogical conditions of its implementation into practice of future teachers' training are revealed; some techniques of forming the readiness to research activities are described.